Study on the Solvent Extraction of Phosphoric Acid from phosphate Ore-HCI Digestion Liquor and Pre-treatment with Amines—Part II - Youssef, N.S.; Hanna, A.A.; Eid, A.E.; EL-Zahany, E.A.M. (Asian Journal of Chemistry, 2010)
The purpose of this work to study the effect of iron content on the solubility of the phosphoric acid produced by dissoluion of Abu-Tartor phosphate ore in HCl at the optimum conditions of dissolution. Also, this work extends to study the pre-treatment of the produced liquor with amines to trap out the iron before extracting and stripping the phosphoric acid. Phase diagrams of organic solvent- H3PO4-H2O systems show that as the iron content increases the solubility of phosphoric acid in the organic solvent decreases. Trioctyl amine (TOA) and tridodecyl amine (TDA) were used to extract iron from the medium of the dissolution. The obtained results indicate that the efficiency of amines to extract iron depends on the molarity of amine, the nature of the diluent, and the concentration of HCl and the length of the hydrocarbon chain of the amine. The mechanism of removing iron by amines in HCl medium was suggested. The analysis of the obtained data show that both trioctyl amine and tridodecyl amine are good extractant to remove about 95% of iron content and TDA is preferable to TOA because it has low concentration (O.I.M./diluent). This may be attributed to the long chain of the hydrocarbon which leads to relatively high amounts of the donor groups. The aromatic diluent is more suitable than the aliphatic one to avoid emulsion formation. It is found that the order of efficiency of the different solvents to extract H3PO4 is: Tret-amyl alcohol > TBP > Bu-OH > DIPA and the order of efficiency of the different reagents to remove iron is: TDA > TOA > DIPA > MIBK > Diethyl ether > (DIPA, 20%).